Analisis Perbandingan Rasio Keuangan Pada Perusahaan Sektor Pariwisata Sebelum dan Di Saat Pandemi COVID-19 - Diva Aqila Nurul Fachira (Indonesian Accounting Literacy Journal, 2022)
The aim of this research was to determine the significant differences between financial ratios before and during the COVID-19 pandemic in tourism sector companies for the 2018-2021 period. The financial ratios used are current ratio, assets turnover, debt to equity ratio (DER), return on investment (ROI), and price earnings ratio. The sample was taken using purposive sampling technique and obtained 19 sample companies. The research method used is a comparative method with a quantitative approach. To test the hypothesis, two different average tests are used, paired sample t-test and wilcoxon signed rank test with SPSS 26. The results of this research are (1) there is a significant difference between the assets turnover and ROI in tourism sector companies before and during the COVID-19 pandemic, (2) there is no significant difference between current ratio, DER, and price earnings ratio in tourism sector companies before and during the COVID-19 pandemic.